Cognitive impairments in cerebrovascular disease: What is between health and dementia? - A. Yu. Emelin (Неврология, нейропсихиатрия, психосоматика, 2015)
The problem of cerebrovascular lesions takes on even greater significance with the higher prevalence of both acute and chronic forms of cerebrovascular diseases (CVD). Cognitive dysfunctions that have a pronounced negative impact on the quality of life in patients hold a special place among the various neurological symptoms resulting from cerebrovascular lesions. The incidence of vascular dementia increases with age. The paper considers the main issues of the etiology, pathogenesis and classification of vascular cognitive impairments (VCIs). It proposes criteria for the diagnosis of VCIs in the early stages of the disease. Potentially modifiable factors, such as hypertension, coronary heart disease, orthostatic hypotension, diabetes mellitus, hypercholesterolemia, hyperhomocysteinemia, obesity, et al., are indicated to have a special place among the main etiological causes of VCIs. The timely detection of etiological factors and the assessment of their role in the development of cognitive impairments (CI) in CVD form the basis for managing these patients. The issues of treating CI no dementia in patients with CVD are considered. These included the administration of nootropic, vasoactive drugs, as well as agents that exert a modulatory effect on the cholinergic and glutamatergic systems. The use of neuroprotective and neurotrophic drugs is noted to be promising in terms of the multicomponent mechanism of their action.